Medical image registration utilizing tissue P systems - Kujur, Saleem Sanatan; Sahana, Sudip Kumar (Frontiers in Pharmacology, 2022)
The Tissue P System (TPS) possesses the intrinsic attributes of parallel execution in comprehensive data and instruction space, which provides fast convergence during the transition from local to global optima. Method- In this paper, the authors have proposed and built a TPSysIR framework using TPS for image registration that optimizes upon the Mutual Information (MI) similarity metric to find a global solution.Result- The model was tested upon single and multimodal brain MRI scans and other prominent optimization-based Image Registration Techniques. Conclusion- Results show that, among all methods, TPSysIR emerges to provide better MI values with minimum deviation in a range of experiment setups conducted iteratively.